Synthesis and Thermal Studies on Copolyesters of Succinoyl Chloride - SULTANA, SAYEEDA; KRISHNAN, SIVARAMA; GUNASEKARAN, S.; RAMAN, T. VENKATA (Asian Journal of Chemistry, 2010)
Co-polyesters of succinoyl chloride were synthesized by condensing two different diols with acid chlorides in o-dichloro benzene at 120-140ºC. Solubility was checked in some common organic solvents and they showed solubility in dimethyl formamide. The thermal analysis of copolyesters was carried out by TGA and DTA studies.